TREATMENT ADHERENCE AS AN ESSENTIAL ELEMENT OF CARDIOVASCULAR DISORDERS MANAGEMENT - D. V. Nebieridze; T. V. Kamyshova; A. S. Safaryan; V. D. Sargsyan (Кардиоваскулярная терапия и профилактика)
The article is focused on the issue of treatment adherence in cardiovascular patients, that is important due to chronic course of cardiovascular diseases (CVD), necessity for long-term therapy and, also, seriously low adherence to treatment in this category of patients. The issues considered, on the objective assessment of adherence. Literature data provided, on the factors influencing adherence. The review focuses on recent data on the solutions of low adherence management in CVD patients. The recommendations given, on the ways for adherence improvement in real clinical practice.